Kinerja keuangan daerah terhadap belanja modal untuk pelayanan publik di Sumatera Bagian Selatan - Nadya Ayu Delima; Taufiq Marwa; Anna Yulianita (Department of Development Economics, Universitas Sriwijaya, 2016)
The analysis in this study aims to determine the effect of regional financial performance which includes regional independence ratios, effectiveness ratios, and efficiency to capital ratios for public services in the South Sumatra Province. The data used in this study are secondary data from the Regional Revenue and Expenditure Budget (APBD) and the realization of the Regional Budget in 2007-2015. The analysis technique used in this study is panel data regression. The results of the study show that: (1) the independence ratio does not have a significant effect on capital expenditure for public services (2) significant effectiveness ratios affect capital expenditure for public services (3) efficiency ratio significantly influences capital expenditure for public services. In conclusion, the three ratios used by South Sumatra have higher intercepts than other provinces. This indicates that South Sumatra has the highest capital expenditure for the highest public services in Sumbagsel.